High-purity quartz lump as well as preparation method and application thereof
By artificially synthesizing high-purity quartz sand as raw material, high-purity quartz lumps are prepared, which solves the problems of high cost and serious pollution caused by impurity residues in natural quartz sand and the silicon tetrachloride method, and realizes the preparation of high-quality, environmentally friendly quartz lumps.
Patent Information
- Application Number
- CN202411264997.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
In the existing quartz weight preparation method, there are impurities residues in natural high-purity quartz sand, which leads to the inability to improve the transmission ratio, hydroxyl content and bubble air line of the quartz glass lump, and the domestic reserves are insufficient; while silicon tetrachloride is used as the raw material. The method is costly and the environmental pollution is severe.
Adopt artificial synthesis of high pure quartz sand as raw materials, prepare high pure quartz pupae through plasma beating, melting casting and other methods to ensure that the total content of impurities is less than 2ppm, a single impurities element content is less than 1ppm, and the transmission ratio of the 165nm deep ultraviolet band is transmitted ratio It is greater than 80%, the hydroxyl content is less than 30 ppm, and there is no bubble and air line.
It improves the quality of quartz crickets, enhances its light transmission performance in deep ultraviolet bands, reduces the hydroxyl content, avoids bubbles and air line defects, and is more environmentally friendly than traditional methods.
Smart Images

Figure CN119349865A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz ingots, and in particular to a high-purity quartz ingot and a preparation method and application thereof. Background Art
[0002] Quartz ingot is an important basic blank for manufacturing various quartz products in the shape of tubes, rods, plates, etc. One important aspect of developing quartz glass technology for the electronic information industry is to improve the manufacturing level and product quality of quartz ingots. In recent years, the electronic information industry application market has put forward higher performance requirements for the required quartz products, so quartz ingot technology is also developing in the direction of "high purity".
[0003] There are currently two main methods for preparing quartz ingots. One is to use natural high-purity quartz as raw material and prepare it through plasma melting, gas refining and other methods. The other is to use silicon tetrachloride as raw material and prepare it through the gas phase method. In the first method, due to the presence of a certain amount of impurities and inclusions in natural high-purity quartz sand, even if it is treated by physical and chemical methods, there is still a certain amount of residue, which makes it impossible to further improve the transmittance, hydroxyl content, bubble gas line and other indicators of the quartz glass ingot. In addition, the domestic reserves of high-purity quartz sand are small and need to be imported in large quantities. The second method uses silicon tetrachloride as raw material for preparation. This method is costly and will cause greater environmental pollution. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high-purity quartz lump and a preparation method thereof, using artificially synthesized high-purity quartz sand as raw material, so that the total content of impurity elements in the obtained quartz lump is less than 2ppm, the content of a single impurity element is less than 1ppm, the transmittance in the 165nm deep ultraviolet band is greater than 80%, the hydroxyl content is less than 30ppm, and there are no bubbles or gas lines.
[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0006] One of the purposes of the present invention is to provide a method for preparing high-purity quartz lumps, using artificially synthesized high-purity quartz sand as raw material.
[0007] The second object of the present invention is to provide a high-purity quartz lump obtained by the above-mentioned preparation method of high-purity quartz lump.
[0008] The third object of the present invention is to provide the application of the high-purity quartz lump in the production of quartz tubes, quartz rods and quartz plates.
[0009] The beneficial effects of the present invention are as follows: compared with the existing quartz ingot prepared by using natural quartz sand, the quartz ingot prepared by the present invention has better quality; compared with the method of preparing quartz ingot using silicon tetrachloride as raw material, the quartz ingot preparation method provided by the present invention is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is the XRD pattern of the glassy high-purity quartz sand prepared in Example 1;
[0011] Figure 2 This is a microscope picture of the glassy high-purity quartz sand prepared in Example 1;
[0012] Figure 3 This is the XRD pattern of the high-purity quartz prepared in Example 5. DETAILED DESCRIPTION
[0013] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0014] The present invention provides a method for preparing high-purity quartz lumps, using artificially synthesized high-purity quartz sand as a raw material. The quartz lumps can be prepared from the artificially synthesized high-purity quartz sand by methods such as plasma lumping and melt casting.
[0015] Furthermore, the artificially synthesized high-purity quartz sand includes two forms: amorphous and crystalline. Preferably, the artificially synthesized high-purity quartz sand includes glassy high-purity quartz sand, high-purity cristobalite, etc. Glassy quartz sand belongs to amorphous quartz sand, and cristobalite belongs to crystalline quartz sand.
[0016] Furthermore, the particle size of the artificially synthesized high-purity quartz sand is greater than 1 μm.
[0017] Furthermore, the purity of the artificially synthesized high-purity quartz sand is greater than 99.9998%. The present invention uses artificially synthesized high-purity quartz sand as a raw material for preparing quartz lumps, which fundamentally solves the problem of high impurity element content in quartz lumps.
[0018] Furthermore, the total content of impurity elements such as K, Na, Li, Ca, Mg, Fe, Al, Cr, Cu, Mn, Ba, and Ti in the artificially synthesized high-purity quartz sand is less than 2 ppm, and the content of a single impurity element is less than 1 ppm.
[0019] The present invention provides a high-purity quartz lump obtained by the above-mentioned preparation method of high-purity quartz lump.
[0020] Furthermore, the total content of impurity elements such as K, Na, Li, Ca, Mg, Fe, Al, Cr, Cu, Mn, Ba, and Ti in the high-purity quartz lump is less than 2 ppm, and the content of a single impurity element is less than 1 ppm.
[0021] Furthermore, the transmittance of the high-purity quartz block in the 165nm deep ultraviolet band is greater than 80%. The quartz block prepared by the present invention exhibits good light transmittance in the deep ultraviolet band and can be used in fields such as photolithography machines that require high transmittance in the deep ultraviolet band.
[0022] Furthermore, the hydroxyl content of the high-purity quartz ingot is less than 30 ppm. The lower the hydroxyl content, the better the temperature resistance of the quartz ingot.
[0023] Furthermore, the high-purity quartz ingot has no bubbles or gas lines. The presence of bubbles and gas lines may cause defects in the quartz ingot in subsequent products.
[0024] The invention provides application of the high-purity quartz lump in the production of quartz tubes, quartz rods and quartz plates.
[0025] The present invention also provides a method for preparing glassy high-purity quartz sand, comprising the following steps:
[0026] S1, adding water to nano-scale amorphous silicon dioxide to prepare a slurry, and spray-drying the slurry to obtain nano-silicon dioxide agglomerates;
[0027] S2, subjecting the nano-silicon dioxide aggregates prepared in step S1 to mechanical static pressing to obtain bulk silicon dioxide;
[0028] S3, crushing, calcining and cooling the bulk silicon dioxide prepared in step S2 to obtain glassy high-purity quartz sand.
[0029] Furthermore, the average particle size of the nano-scale amorphous silicon dioxide is 5-100 nm. Amorphous silicon dioxide is a non-crystalline silicon dioxide. The present invention uses nano-scale amorphous silicon dioxide as a raw material to prepare glassy high-purity quartz sand. High-purity quartz sand in nature is crystalline, while the high-purity quartz sand prepared by the present invention is glassy, which belongs to amorphous state and has a relatively low processing temperature.
[0030] Furthermore, the solid content of the slurry is 5-50%. In the present invention, if the solid content is lower than the range, the powder obtained by spray drying has more fine particles and poor fluidity; if the solid content is higher than the range, the viscosity of the slurry is high and the nozzle is easily blocked.
[0031] Furthermore, the air inlet temperature of the spray drying is 280-350° C., and the air outlet temperature is 80-120° C. In the present invention, the nano-scale amorphous silicon dioxide is transformed into nano-silicon dioxide agglomerates by spray drying.
[0032] Furthermore, the average particle size of the nano-silicon dioxide agglomerates is 100-500 μm. If the particle size is too large, the uniformity will be poor; if the particle size is too small, it will be difficult to prepare. Of course, the particle size of the nano-silicon dioxide agglomerates is also affected by the particle size of the raw material nano-scale amorphous silicon dioxide.
[0033] Furthermore, the pressure of the mechanical static pressure is 150-250MPa, and the time is 10-40min. Since the nano-silicon dioxide powder is very fluffy, if pressure is directly applied to the powder, it will expand again and become loose when the pressure is released, so it is necessary to add water to make a slurry first, and then make large particles by spray drying. In the present invention, the role of mechanical static pressure is to overcome the repulsive force between the nano-silicon dioxide particles, so that the distance between the nano-silicon dioxide particles is closer, so that the product obtained after sintering has less pores.
[0034] Furthermore, the average particle size of the blocky silicon dioxide after mechanical crushing is 50-400 μm.
[0035] Furthermore, the calcination temperature is 1000-1600°C and the time is 3-8h. The crushed blocky silicon dioxide is densified by calcination. If the calcination temperature is too high or the calcination time is too long, crystallization will occur and the energy consumption will be high; if the calcination temperature is too low or the calcination time is too short, it cannot be completely melted and the obtained product has a porous structure. Preferably, the calcination temperature is 1100-1200°C and the time is 5-6h.
[0036] Example 1
[0037] Amorphous silicon dioxide with a D50 particle size of 10 nm is added to water to prepare a slurry with a solid content of 20%; the slurry is spray-dried (the inlet air temperature is 280° C., the outlet air temperature is 80° C.) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 150 μm; the nano-silicon dioxide agglomerates are mechanically statically pressed (the pressure is 200 MPa, and the time is 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with a D50 particle size of 70 μm, calcined at 1100° C. for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with a D50 particle size of 30 μm.
[0038] The glassy high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0039] Example 2
[0040] Amorphous silicon dioxide with a D50 particle size of 25 nm is added to water to prepare a slurry with a solid content of 5%; the slurry is spray-dried (the inlet air temperature is 350° C. and the outlet air temperature is 120° C.) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 300 μm; the nano-silicon dioxide agglomerates are mechanically statically pressed (the pressure is 250 MPa and the time is 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with a D50 particle size of 80 μm, calcined at 1200° C. for 5 h, and naturally cooled to obtain glassy high-purity quartz sand with a D50 particle size of 45 μm.
[0041] The glassy high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0042] Example 3
[0043] Amorphous silicon dioxide with a D50 particle size of 90 nm is added to water to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 280° C. and the outlet air temperature is 80° C.) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 500 μm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa for 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with a D50 particle size of 90 μm, calcined at 1200° C. for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with a D50 particle size of 50 μm.
[0044] The glassy high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0045] Example 4
[0046] Amorphous silicon dioxide with a D50 particle size of 65 nm is added to water to prepare a slurry with a solid content of 50%; the slurry is spray-dried (the inlet air temperature is 280° C., the outlet air temperature is 80° C.) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 200 μm; the nano-silicon dioxide agglomerates are mechanically statically pressed (the pressure is 200 MPa, and the time is 0.5 h) to obtain block silicon dioxide; the block silicon dioxide is mechanically crushed into particles with a D50 particle size of 70 μm, calcined at 1100° C. for 6 h, and naturally cooled to obtain glassy high-purity quartz sand with a D50 particle size of 50 μm.
[0047] The glassy high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0048] Example 5
[0049] 3 kg of D50 with a particle size of 8 nm and a specific surface area of 150 m 2 / g of amorphous silicon dioxide was dried at 100°C for 2h, and 30g of coupling agent (CH3O)3Si(CH2) 10 CH3 was mixed with 100 g of ethanol to obtain a modified liquid, which was evenly mixed with the dried amorphous silicon dioxide, dried at 100°C for 2 h, calcined at 1170°C for 10 h, cooled naturally, and dispersed with air flow to obtain high-purity cristobalite with a D50 particle size of 176 μm.
[0050] High purity quartz is melted at 2000℃ to obtain high purity quartz ingot.
[0051] Comparative Example 1
[0052] High-purity quartz sand of model ITOA-6 produced by Unimin Corporation of the United States is used as the raw material for preparing quartz ingot.
[0053] High-purity quartz sand is melted at 2000℃ to obtain high-purity quartz ingot.
[0054] Comparative Example 2
[0055] The preparation method of quartz sand is the same as that of Example 1, except that spray drying is not performed.
[0056] Amorphous silica with a D50 particle size of 10 nm is subjected to mechanical static pressure (pressure of 200 MPa, time of 0.5 h) to obtain bulk silica; after pressure release, the bulk silica cracks, and the bulk silica is mechanically crushed into particles with a D50 particle size of 70 μm, calcined at 1100°C for 6 h, and naturally cooled to obtain opaque high-purity quartz sand with a D50 particle size of 30 μm.
[0057] The opaque high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0058] Comparative Example 3
[0059] The preparation method of quartz sand is the same as that of Example 1, except that mechanical static pressure is not performed.
[0060] Amorphous silicon dioxide with a D50 particle size of 10 nm is added to water to prepare a slurry with a solid content of 20%; the slurry is spray-dried (the inlet air temperature is 280°C and the outlet air temperature is 80°C) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 150 μm; the nano-silicon dioxide agglomerates are calcined at 1100°C for 6 hours and naturally cooled to obtain opaque high-purity quartz sand with a D50 particle size of 78 μm.
[0061] The opaque high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0062] Comparative Example 4
[0063] The preparation method of quartz sand is the same as that of Example 3, except that spray drying is not performed.
[0064] Amorphous silicon dioxide with a D50 particle size of 90 nm is subjected to mechanical static pressure (pressure of 150 MPa, time of 0.5 h) to obtain bulk silicon dioxide; after pressure relief, the bulk silicon dioxide cracks, and the bulk silicon dioxide is mechanically crushed into particles with a D50 particle size of 90 μm, calcined at 1200°C for 6 h, and naturally cooled to obtain opaque high-purity quartz sand with a D50 particle size of 50 μm.
[0065] The opaque high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0066] Comparative Example 5
[0067] The preparation method of quartz sand is the same as that of Example 3, except that mechanical static pressure is not performed.
[0068] Amorphous silicon dioxide with a D50 particle size of 90 nm is added to water to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 280°C and the outlet air temperature is 80°C) to obtain nano-silicon dioxide agglomerates with a D50 particle size of 500 μm; the nano-silicon dioxide is calcined at 1200°C for 6 hours and naturally cooled to obtain opaque high-purity quartz sand with a D50 particle size of 380 μm.
[0069] The opaque high-purity quartz sand is melted at 2000℃ to obtain a high-purity quartz ingot.
[0070] from Figure 1-3 It can be seen that Example 1 prepared glassy quartz sand, Example 5 prepared cristobalite, and Comparative Examples 2-5 prepared opaque quartz sand.
[0071] The quartz sand and cristobalite prepared in the above Examples 1-5 and Comparative Examples 2-5 and the high-purity quartz sand in Comparative Example 1 were detected for impurity ions using ICP-OES (inductively coupled plasma emission spectrometer) with a detection limit of 1 ppb. The results are shown in Table 1.
[0072] Table 1 Impurity ion test results of quartz sand and cristobalite (unit: ppm)
[0073]
[0074]
[0075] It can be seen from Table 1 that, compared with commercially available natural high-purity quartz sand, the glassy quartz sand and cristobalite prepared in Examples 1-5 of the present invention have higher purity, and the total content of impurity elements is less than 2 ppm.
[0076] The quartz ingot samples prepared in the above examples and comparative examples were detected for impurity ions using ICP-OES (inductively coupled plasma optical emission spectrometer) with a detection limit of 1 ppb. The results are shown in Table 2.
[0077] Table 2 Impurity ion test results of quartz ingot samples (unit: ppm)
[0078]
[0079]
[0080] It can be seen from Table 2 that, compared with commercially available high-purity quartz sand, the quartz ingot prepared by the present invention using artificially synthesized glassy high-purity quartz sand and high-purity cristobalite as raw materials has a lower total content of impurity elements (less than 2 ppm), that is, the purity of the quartz ingot is higher.
[0081] The transmittance, hydroxyl content and bubble mark tests of the quartz ingot samples prepared in the above embodiments and comparative examples were performed in accordance with JC / T185-2013, GB / T12442-2019 and JC / T2392-2017. The results are shown in Table 3.
[0082] Table 3 Test results of transmittance, hydroxyl content and bubble marks of quartz ingot samples
[0083]
[0084] As can be seen from Table 3, compared with commercially available high-purity quartz sand, the quartz ingot prepared by the present invention using artificially synthesized glassy high-purity quartz sand and high-purity cristobalite as raw materials has a large ultraviolet light transmittance, a small hydroxyl content, and few bubble defects. The main reason is that the artificially synthesized high-purity quartz sand of the present invention has high purity and does not contain gas-liquid inclusions. Comparative Examples 2-5 Since the obtained high-purity quartz sand is porous and opaque, it is still porous after being melted into a quartz ingot, and the number of bubbles cannot be tested, and the ultraviolet light transmittance is relatively small.
[0085] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing high-purity quartz lump, characterized in that: Artificially synthesized high-purity quartz sand is used as raw material; the artificially synthesized high-purity quartz sand includes glassy high-purity quartz sand and high-purity cristobalite.
2. The preparation method according to claim 1, characterized in that: The particle size of the artificially synthesized high-purity quartz sand is greater than 1 μm.
3. The preparation method according to claim 1, characterized in that: The purity of the artificially synthesized high-purity quartz sand is greater than 99.9998%.
4. The preparation method according to claim 1, characterized in that: The total content of impurity elements in the artificially synthesized high-purity quartz sand is less than 2 ppm, and the content of a single impurity element is less than 1 ppm.
5. A high-purity quartz lump prepared by the preparation method according to any one of claims 1 to 4.
6. The high-purity quartz lump according to claim 5, characterized in that: The total content of impurity elements in the high-purity quartz lump is less than 2 ppm, and the content of a single impurity element is less than 1 ppm.
7. The high-purity quartz lump according to claim 5, characterized in that: The transmittance of the high-purity quartz lump in the 165nm deep ultraviolet band is greater than 80%.
8. The high-purity quartz lump according to claim 5, characterized in that: The hydroxyl content of the high-purity quartz ingot is less than 30 ppm.
9. The high-purity quartz lump according to claim 5, characterized in that: The high-purity quartz ingot has no bubbles or gas lines.
10. Use of the high-purity quartz lump described in any one of claims 5 to 9 in the production of quartz tubes, quartz rods and quartz plates.
Citation Information
Patent Citations
Preparation method of low-hydroxyl solid quartz steelyard weight
CN103265162A
Method for preparing glassy state transparent quartz sand
CN104909558A
Preparation method of quartz lead
CN109160724A
Manufacturing device of opaque quartz weight
CN115180807A
High-purity quartz sand and preparation method thereof
CN116654945A
Cited By
Quartz crucible for monocrystalline silicon production and preparation method thereof
CN120485938A